2018
DOI: 10.1097/prs.0000000000004231
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Alveolar Segment Position as a Predictor of Successful Gingivoperiosteoplasty in Patients with Unilateral Cleft Lip and Palate

Abstract: Risk, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Velopharyngeal insufficiency requires highly coordinated care and clear communication between speech/language pathologists and surgeons (Ruda et al, 2012). Alveolar bone grafting and orthognathic surgery are 2 other procedures that demand strong partnerships between surgeons and dentists/orthodontists to optimize timing and outcomes (Dec et al, 2013; Esenlik et al, 2017). The observation that these procedures are predominantly performed by teams suggests that their provision is facilitated by the high levels of coordination and communication that are required by the Standards of ACPA team approval.…”
Section: Discussionmentioning
confidence: 99%
“…Velopharyngeal insufficiency requires highly coordinated care and clear communication between speech/language pathologists and surgeons (Ruda et al, 2012). Alveolar bone grafting and orthognathic surgery are 2 other procedures that demand strong partnerships between surgeons and dentists/orthodontists to optimize timing and outcomes (Dec et al, 2013; Esenlik et al, 2017). The observation that these procedures are predominantly performed by teams suggests that their provision is facilitated by the high levels of coordination and communication that are required by the Standards of ACPA team approval.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the unfavorable growth following GPP without presurgical infant orthopedic preparation (Rintala & Ranta, 1989; Renkielska et al, 2005). In studies of patients prepared for GPP with presurgical infant orthopedics, it has been recommended that the alveolar cleft gap width should be less than 1.7 mm for a successful primary GPP procedure (Esenlik et al, 2018). In infants with bilateral cleft lip and palate, primary GPP may be considered with wider alveolar cleft gaps, as premaxilla mobility allows the surgeon to gently reposition the premaxilla to one side and perform GPP at least unilaterally (Traube et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Grayson and Cutting later describe the use of NasoAlveolar Molding (NAM) as a method of passively narrowing the width between alveolar cleft segments to 1 to 2 mm followed by GPP at time of cleft lip repair. 10,11 Although good bony restoration has been demonstrated with this technique, long term growth outcomes are pending.…”
Section: Introductionmentioning
confidence: 99%
“…13 GPP can be an effective method of alveolar cleft repair in as high as 72% of patients, 14 obviating the need for secondary bone grafting. 7,11 Currently, there are no large scale studies reporting on national trends in GPP. The purpose of our study is to investigate national trends in GPP, demographics of children undergoing GPP, short term surgical outcomes, and operative time with addition of GPP when compared to cleft lip repair alone.…”
Section: Introductionmentioning
confidence: 99%